Corporate Monarchy in the Twelfth-Century Kingdom of Jerusalem - Erin Jordan (Royal Studies Journal, 2019)
While the conflicts between Queen Melisende of Jerusalem and the men in her family have received considerable scholarly attention, explanations for the ease with which they reconciled remain elusive. As this article argues, contrary to theories advanced in the past, Melisende’s role in government was not the product of a consensus among nobles to temporarily suspend the norms of political participation that invested all authority in a single, male, ruler. The position she occupied was not “exceptional,” a disruption in the fabric of patriarchal dynastic succession that cloaked the Latin East. Rather, she occupied a legitimate position as co-ruler of the Kingdom, filling the role envisioned for her by her father, Baldwin II, who recognized in corporate monarchy an ideal political configuration for the challenges presented by governing in the Latin East. Past failures to provide an accurate and complete understanding of Melisende’s role in the governance of Jerusalem has circumscribed our understanding of the nature of monarchy and rulership in this crusader kingdom, which remains inaccurate and incomplete as a result. In their attempt to impose a uniform, static template of feudal governance on the crusader kingdoms of Latin East, scholars have under appreciated the extent to which medieval monarchy was both fluid and contingent. As the discussion here demonstrates, modes of governing were constantly adjusted to the demands of a particular time and place, responding to the unique political culture of a particular region. This was especially true for monarchy in the nascent crusader kingdom of twelfth-century Jerusalem, which witnessed the evolution of a political system formed in the crucible of war.